Narzędzia informatyczne wspomagające zarządzanie bezpieczeństwem systemu informacyjnego - Rot, Artur (Software implementations supporting information system security management, 2005)
The rapid progress in the area of information technology brings new threats of information disclosure. The subject of IS/IT security has become very significant. Every organisation has to apply adequate methods, tools and organisational requirements to protect its information resources. The aim of this article is to present the essence and the importance of the information system security management. The paper also presents the software applications, which support information system security management processes. The information security isn’t complete without the development and publication of security policies, procedures and processes like employee awareness and training programs. The information security is really an ongoing management process and therefore requires tools that meet these needs. One of these tools is software applications, supporting information security management, based on the international standard ISO 17799. Two of these applications will be presented - Callio Secura is a software that helps companies comply with the BS7799/ ISO IEC 17799 information security management standard. It helps to develop, implement, manage and certify information security management system (ISMS) in accordance with this standard. The second presented application - Proteus ISMS is the system, which supports all phases and aspects of ISMS in accordance with the discussed standard.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (8); 2005; nr 1094, s. 259-269